THE EFFECTIVENESS OF THE 5E LEARNING CYCLE MODEL AS AN EFFORT TO OPTIMIZE STUDENTS' ACTIVITIES AND LEARNING OUTCOMES - Muhammad Amin Lasaiba (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
The learning model is something framework that describes stages systematically with the main attention to students as the center point (student-centered) in learning. Study this focusing on the learning cycle model which is a set of activity stages that can contribute to the mastery of competencies achieved by students in activity-oriented teaching and learning activities. Method research used is Classroom Action Research (CAR) and location research at SMA Muhammadiyah Ambon. The sample used is selected from class XI by random sampling. Research Results show that the model 5E learning cycle can improve student activity and learning outcomes. Mastery learning from cognitive tests increased in First Cycle to Second Cycle. In the first cycle obtained 72.5% and an increase in the second cycle 85.0%. Performance appraisal also increased, namely in the first cycle by 75.0% and in the second cycle by 87.5%. The achievement of research success criteria in Second Cycle, both in terms of applying the model in learning, the learning process which includes teacher and student activities, as well as student learning outcomes in cognitive, affective, and psychomotor, and this research was successful and ended in Second Cycle.